Enhanced growth and osteogenic differentiation of human osteoblast-like cells on boron-doped nanocrystalline diamond thin films - Grausova, Lubica; Kromka, Alexander; Burdikova, Zuzana; Eckhardt, Adam; Rezek, Bohuslav; Vacik, Jiri; Haenen, Ken; Lisa, Vera; Bacakova, Lucie (PloS one, 2011)
Intrinsic nanocrystalline diamond (NCD) films have been proven to be promising substrates for the adhesion, growth and osteogenic differentiation of bone-derived cells. To understand the role of various degrees of doping (semiconducting to metallic-like), the NCD films were deposited on silicon substrates by a microwave plasma-enhanced CVD process and their boron doping was achieved by adding trimethylboron to the CH(4):H(2) gas mixture, the B∶C ratio was 133, 1000 and 6700 ppm. The room temperature electrical resistivity of the films decreased from >10 MΩ (undoped films) to 55 kΩ, 0.6 kΩ, and 0.3 kΩ (doped films with 133, 1000 and 6700 ppm of B, respectively). The increase in the number of human osteoblast-like MG 63 cells in 7-day-old cultures on NCD films was most apparent on the NCD films doped with 133 and 1000 ppm of B (153,000 ± 14,000 and 152,000 ± 10,000 cells/cm(2), respectively, compared to 113,000 ± 10,000 cells/cm(2) on undoped NCD films). As measured by ELISA per mg of total protein, the cells on NCD with 133 and 1000 ppm of B also contained the highest concentrations of collagen I and alkaline phosphatase, respectively. On the NCD films with 6700 ppm of B, the cells contained the highest concentration of focal adhesion protein vinculin, and the highest amount of collagen I was adsorbed. The concentration of osteocalcin also increased with increasing level of B doping. The cell viability on all tested NCD films was almost 100%. Measurements of the concentration of ICAM-1, i.e. an immunoglobuline adhesion molecule binding inflammatory cells, suggested that the cells on the NCD films did not undergo significant immune activation. Thus, the potential of NCD films for bone tissue regeneration can be further enhanced and tailored by B doping and that B doping up to metallic-like levels is not detrimental for cells.
Keywords: fyzikální jevy; buněčná diferenciace; Cell Survival; bor; Humans; osteogeneze; kolagen typu I; Osteogenesis; osteoblasty; Dose-Response Relationship, Drug; Collagen Type I; Cell Adhesion; polovodiče; lidé; Nanostructures; Osteoblasts; zvířata; proliferace buněk; Physical Phenomena; nanostruktury; buněčné linie; Adsorption; Cell Line; Diamond; Boron; Cell Proliferation; Cell Differentiation; diamant; vztah mezi dávkou a účinkem léčiva; Semiconductors; Animals; buněčná adheze; Silicon; adsorpce; viabilita buněk; křemík